An Overview of the Homozygous Cystic Fibrosis Transmembrane Conductance Regulator Mutation c.3700 A>G (p.Ile1234Val) in Qatar - Samer Hammoudeh (3095097) (2019)
Purpose of Review Cystic fibrosis (CF) is a monogenic recessive disease with multisystem involvement. The cause is a mutation in the gene that encodes the cystic fibrosis transmembrane conductance regulator (CFTR) protein. The aim is to review the literature involving the CFTR I1234V mutation and to provide recommendations for future research activities. Recent Findings The prevalence rates of CFTR mutations vary across the globe. The CFTR I1234V mutation is the most common mutation in Qatar, and one of the most common in the Arabian Gulf region. Summary Areas for future research include testing of the CFTR transcript and activity levels in different samples including nasal cells and organoids. Another area is applying Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology as a tool for gene editing. Other Information Published in: Current Genetic Medicine Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40142-019-00174-7